Upaya Guru dalam Melestarikan Nilai Kebudayaan Lokal Melalui Mata Pelajaran IPS Tahun 2019/2020 - Itsna Yusriya (Institut Agama Islam Negeri Jember, 2021)
Abstract Culture is a complex whole that contains knowledge, beliefs, arts, morals, customary law and other abilities, and habits acquired by humans as members of society. The creation of culture is inseparable from the process of social interaction between individuals, groups, or individuals and groups. Social interaction is the most real reality in human life. The purpose of this study is to describe the efforts of teachers in preserving local cultural values ??through social studies subjects in MTs Kebunrejo, Banyuwangi Regency and describing teachers' efforts to internalize local cultural values ??through social studies in MTs Kebunrejo Banyuwangi Regency. This study employs a qualitative approach descriptive research. Data was collected through observation, interviews and documentation. And the validity of the data was done by triangulation of sources and triangulation of techniques. The results of the study show that teachers efforts in preserving local cultural values ??in MTs Kebunrejo is through the learning process in the classroom which includes three stages of activity namely the preparation phase, the implementation phase and the evaluation phase. Teachers efforts in internalizing local culture in MTs Kebunrejo that is by incorporating local culture through learning material being taught and involving students in cultural events such as dancing gandrung dances in festivals in the districts and districts as well as participating in cultural activities in schools.